NMR‐based metabolomics and breath studies show lipid and protein catabolism during low dose chronic T1AM treatment. (29th May 2013) - Haviland, J.A.; Reiland, H.; Butz, D.E.; Tonelli, M.; Porter, W.P.; Zucchi, R.; Scanlan, T.S.; Chiellini, G.; Assadi‐Porter, F.M.
<x xml:space="preserve">Abstract</x> Objective 3‐Iodothyronamine (T1AM), an analog of thyroid hormone, is a recently discovered fast‐acting endogenous metabolite. Single high‐dose treatments of T1AM have produced rapid short‐term effects, including a reduction of body temperature, bradycardia, and hyperglycemia in mice. Design and Methods The effect of daily low doses of T1AM (10 mg/kg) for 8 days on weight loss and metabolism in spontaneously overweight mice was monitored. The experiments were repeated twice (n = 4). Nuclear magnetic resonance (NMR) spectroscopy of plasma and real‐time analysis of exhaled 13CO2 in breath by cavity ring down spectroscopy (CRDS) were used to detect T1AM‐induced lipolysis. Results CRDS detected increased lipolysis in breath shortly after T1AM administration that was associated with a significant weight loss but independent of food consumption. NMR spectroscopy revealed alterations in key metabolites in serum: valine, glycine, and 3‐hydroxybutyrate, suggesting that the subchronic effects of T1AM include both lipolysis and protein breakdown. After discontinuation of T1AM treatment, mice regained only 1.8% of the lost weight in the following 2 weeks, indicating lasting effects of T1AM on weight maintenance. Conclusions CRDS in combination with NMR and 13C‐metabolic tracing constitute a powerful method of investigation in obesity studies for identifying in vivo biochemical pathway shifts and unanticipated debilitating side effects.